Generation and characterization of an Nse-CreERT2 transgenic line suitable for inducible gene manipulation in cerebellar granule cells. - Theresa Pohlkamp; Laura Steller; Petra May; Thomas Günther; Roland Schüle; Michael Frotscher; Joachim Herz; Hans H Bock (PLoS ONE, 2014)
We created an Nse-CreERT2 mouse line expressing the tamoxifen-inducible CreERT2 recombinase under the control of the neuron-specific enolase (Nse) promoter. By using Cre reporter lines we could show that this Nse-CreERT2 line has recombination activity in the granule cells of all cerebellar lobules as well as in postmitotic granule cell precursors in the external granular layer of the developing cerebellum. A few hippocampal dentate gyrus granule cells showed Cre-mediated recombination as well. Cre activity could be induced in both the developing and adult mouse brain. The established mouse line constitutes a valuable tool to study the function of genes expressed by cerebellar granule cells in the developing and adult brain. In combination with reporter lines it is a useful model to analyze the development and maintenance of the cerebellar architecture including granule cell distribution, migration, and the extension of granule cell fibers in vivo.